In vitro activity of imipenem/relebactam against Gram-negative ESKAPE pathogens isolated in 17 European countries: 2015 SMART surveillance programme. (11th April 2018) - Karlowsky, James A; Lob, Sibylle H; Kazmierczak, Krystyna M; Hawser, Stephen P; Magnet, Sophie; Young, Katherine; Motyl, Mary R; Sahm, Daniel F
Abstract: Objectives: Relebactam is an inhibitor of class A β-lactamases, including KPC β-lactamases, and class C β-lactamases, and is currently under clinical development in combination with imipenem. The objective of the current study was to evaluate the in vitro activity of imipenem/relebactam against Gram-negative ESKAPE pathogens ( Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter spp.) submitted by clinical laboratories in 17 European countries to the Study for Monitoring Antimicrobial Resistance Trends (SMART) global surveillance programme in 2015. Methods: MICs were determined using the CLSI standard broth microdilution method and interpreted using EUCAST clinical breakpoints. Relebactam was tested at a fixed concentration of 4 mg/L in combination with doubling dilutions of imipenem. Imipenem/relebactam MICs were interpreted using breakpoints for imipenem. Results: Rates of susceptibility to imipenem and imipenem/relebactam for isolates of P. aeruginosa ( n  =   1705), K. pneumoniae ( n  =   1591) and Enterobacter spp. ( n  =   772) were 72.0/94.7%, 88.7/94.8% and 95.6/96.8%, respectively. Relebactam restored imipenem susceptibility to 81.1%, 54.2% and 26.5% of imipenem-non-susceptible isolates of P. aeruginosa ( n  =   477), K. pneumoniae ( n  =   179) and Enterobacter spp. ( n  =   34). Most imipenem/relebactam-non-susceptible isolates carried MBLs, OXA-48 or GES carbapenemases. Relebactam did not increase the number of isolates of A. baumannii ( n  =   486) susceptible to imipenem. Conclusions: Relebactam restored susceptibility to imipenem for the majority of imipenem-non-susceptible isolates of P. aeruginosa and K. pneumoniae tested as well as some isolates of imipenem-non-susceptible Enterobacter spp. Based on our results, imipenem/relebactam appears to be a promising therapeutic option for treating patients with infections caused by antimicrobial-resistant Gram-negative bacilli.